2020
DOI: 10.1111/gcb.15324
|View full text |Cite
|
Sign up to set email alerts
|

Projected expansion of Trichodesmium’s geographical distribution and increase in growth potential in response to climate change

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 82 publications
2
7
0
Order By: Relevance
“…Trichodesmium may increase by up to 173% by 2100 (Boatman et al, 2020). The study by Boatman et al (2020) also indicated that the thermal niche of Trichodesmium will likely expand at high latitudes and reduce in equatorial regions, agreeing with the findings of this study.…”
Section: Responses To Warmingsupporting
confidence: 90%
See 4 more Smart Citations
“…Trichodesmium may increase by up to 173% by 2100 (Boatman et al, 2020). The study by Boatman et al (2020) also indicated that the thermal niche of Trichodesmium will likely expand at high latitudes and reduce in equatorial regions, agreeing with the findings of this study.…”
Section: Responses To Warmingsupporting
confidence: 90%
“…Trichodesmium may increase by up to 173% by 2100 (Boatman et al, 2020). The study by Boatman et al (2020) also indicated that the thermal niche of Trichodesmium will likely expand at high latitudes and reduce in equatorial regions, agreeing with the findings of this study. It is worth noting however, that under lower emissions scenarios, the associated reduction in warming would reduce the extent of thermal stress for both diazotrophs by 12%-17% compared to the high emissions RCP8.5 scenario (Table 2; Figure S3).…”
Section: Responses To Warmingsupporting
confidence: 90%
See 3 more Smart Citations